The Global Determinants of International Equity Risk Premiums - Londono, Juan M.; Xu, Nancy R. (Management Science, 2023)
We examine the commonalities in international equity risk premiums by linking empirical evidence for the ability of U.S. downside and upside variance risk premiums (DVP and UVP, respectively) to predict international stock returns with implications from an empirical model featuring asymmetric economic uncertainty and risk aversion. We find that DVP and UVP predict international stock returns through U.S. bad and good macroeconomic uncertainties, respectively. Sixty percent to 80% of the dynamics of the global equity risk premium for horizons under seven months are driven by economic uncertainty, whereas risk aversion appears more relevant for longer horizons. The predictability patterns of DVP and UVP vary across countries depending on those countries’ financial and economic exposure to global shocks. In those with higher economic exposure, investors demand higher compensation for bad macroeconomic uncertainty but lower compensation for good macroeconomic uncertainty, whereas the compensation for bad macroeconomic uncertainty is lower for countries with high financial exposure. This paper was accepted by Lukas Schmid, finance. Supplemental Material: The data and online appendices are available at https://doi.org/10.1287/mnsc.2023.4958 .